Improving the culture of performing competitive compositions by young gymnasts through the use of non-traditional means of training - Sutula, V.; Deyneko, A.; Riabchenko, O. (Slobozhanskyi herald of science and sport, 2019)
Purpose: to develop and evaluate the effectiveness of methods for improving the culture of young gymnasts performing competitive compositions through the use of non-traditional means of training in the training process.